Cryptotia in a Western adult patient: A case report - Jonathan Augusto Vidal Oliveira; Alberto Ferraz de Melo; Luiz Alberto de Souza Leite; Carlos Lacerda De Andrade Almeida; Letícia Kelly Domingos Brito; Evelliny Gomes da Silva; Antônio Lucas do Nascimento Silva; José Igor Moura de Arruda (Revista Brasileira de Cirurgia Plástica, 2019)
Introduction: Cryptotia is a congenital ear deformity common in Easterners and rare in Westerners, with most studies addressing Eastern surgical techniques applied to children. In this pathology, the cartilage of the upper pole of the ear is lodged subcutaneously in the temporal region, which prevents individuals from using glasses due to lack of support and prevents esthetic definition of the upper pole. Objective: The present study aimed to report the case of an adult patient with cryptotia undergoing surgical treatment using a mastoid subcutaneous pedicle flap and review the main techniques described for the treatment of this involvement. Conclusion: The subcutaneous pedicle flap described by Yoshimura proved to be adequate for correcting cryptotia in a Western adult patient.